Complex mode of inheritance in holoprosencephaly revealed by whole exome sequencing. Issue 6 (16th February 2016) - Mouden, C.; Dubourg, C.; Carré, W.; Rose, S.; Quelin, C.; Akloul, L.; Hamdi‐Rozé, H.; Viot, G.; Salhi, H.; Darnault, P.; Odent, S.; Dupé, V.; et al.
Abstract : Holoprosencephaly (HPE) is the most common congenital cerebral malformation, characterized by impaired forebrain cleavage and midline facial anomalies. Heterozygous mutations in 14 genes have been associated with HPE and are often inherited from an unaffected parent, underlying complex genetic bases. It is now emerging that HPE may result from a combination of multiple genetic events, rather than from a single heterozygous mutation. To explore this hypothesis, we undertook whole exome sequencing and targeted high‐throughput sequencing approaches to identify mutations in HPE subjects. Here, we report two HPE families in which two mutations are implicated in the disease. In the first family presenting two foetuses with alobar and semi‐lobar HPE, we found mutations in two genes involved in HPE, SHH and DISP1, inherited respectively from the father and the mother. The second reported case is a family with a 9‐year‐old girl presenting lobar HPE, harbouring two compound heterozygous mutations in DISP1 . Together, these cases of digenic inheritance and autosomal recessive HPE suggest that in some families, several genetic events are necessary to cause HPE. This study highlights the complexity of HPE inheritance and has to be taken into account by clinicians to improve HPE genetic counselling. Abstract :